2018
DOI: 10.26719/2018.24.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Health research institutional mapping: an Eastern Mediterranean Regional perspective

Abstract: IntroductionHealth research is an integral component in developing health systems, understanding the roots and consequences of poor health, as well as anticipating and mitigating the effects of various factors on health. Promoting and fostering an environment conducive for health research is mandatory for planning, designing and implementing research and for sharing, using and translating its findings into evidence-informed health policies and cost-effective interventions (1).Mapping studies have been attempte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Several studies have highlighted the important role of international organisations and external donor resources in funding HPSR through project grants in the EMR. 23,24 Although external donor resources are a potential source of HPSR funding, the capacity to develop strong proposals to compete for these funds is weak in the EMR, limiting opportunities to tap into international competitive funding opportunities for HPSR. For instance, in a cross-sectional survey of institutions undertaking health research in EMR countries, most institutions reported submitting less than 10 proposals to national, regional or international sources, and mainly in response to calls for proposals.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have highlighted the important role of international organisations and external donor resources in funding HPSR through project grants in the EMR. 23,24 Although external donor resources are a potential source of HPSR funding, the capacity to develop strong proposals to compete for these funds is weak in the EMR, limiting opportunities to tap into international competitive funding opportunities for HPSR. For instance, in a cross-sectional survey of institutions undertaking health research in EMR countries, most institutions reported submitting less than 10 proposals to national, regional or international sources, and mainly in response to calls for proposals.…”
Section: Resultsmentioning
confidence: 99%
“…This needs to be explored further to understand the source of reporting, whether institutional or by authors themselves, considering the type of publication. In a survey for research institutions in the EMR, including Syria, limited national funding for health research was reported by the majority of institutions [ 19 ]. This is in line with our findings where less than a third of the articles were reported as funded and with no significant changes in-conflict.…”
Section: Discussionmentioning
confidence: 99%
“…The region is comprised of 22 countries and is home to nearly 645 million people -about 9% of the world's population (12), yet the highest representation for the Region was 4%, back in 2010 ( Figure 1). This should not come as a surprise given the comparatively limited research being done in the Region in general, and the dearth of health policy and health systems research in particular (13). This poor research output can be understood in the context of various challenges being faced by EMR countries.…”
Section: Commentarymentioning
confidence: 99%